Application of Kansei engineering to Turkish coffee makers: Connections between hedonic factors and design features. Issue 1 (31st December 2023) - Göken, Müge; Alppay, E. Cem
Abstract: The market share of small household appliances has grown tremendously in recent years. Varied innovation methods are applied in developing small household appliances, including Turkish Coffee Makers; however, Kansei Engineering has not yet been carried out in this field. This paper aims to conduct Kansei Engineering methodology on these machines to provide design inputs for industrial designers. The domain of the study is Turkish Coffee Makers with one pot and without a water tank, and the target is between 20–40 aged Turkish people. 382 participants attended the study, and 16 stimuli were utilised. The study methods are extracting Kansei words, selecting product properties, affinity diagram, SD Questionnaire, factor, descriptive, and PLS analyses. The results suggest that designers can generate Turkish Coffee Makers with Square with fillet as the top view, Trapezoid as the front view, C-shape cornered as the right view, and two colours as the main body colour; and design these products depending on the design factors of stylish, easy to use, joyful, trend follower, functional, desirable, youthful, dissimilar, and luxurious to succeed in the market. As a result, product designers might determine the product properties more efficiently via the findings of this study.